Histological and histochemical characterization on stomach of Mystus cavasius (Hamilton), Oreochromis niloticus (Linnaeus) and Gudusia chapra (Hamilton): Comparative study - Saroj K. Ghosh; Padmanabha Chakrabarti (Journal of Basic and Applied Zoology, 2015)
The histological features and histochemical characterization of the stomach were investigated in Mystus cavasius (Hamilton), Oreochromis niloticus (Linnaeus) and Gudusia chapra (Hamilton) having different feeding habits. Histologically the stomach of all the three fishes was made up of mucosa, submucosa, muscularis and serosa. The mucosa of superficial epithelium consists of a single layer of compactly arranged columnar epithelial cells. Prominent gastric glands are present in M. cavasius whereas in G. chapra the gastric glands are totally absent in the gizzard like stomach. However, in O. niloticus tubular gastric glands are present in the glandular epithelium of caecal like stomach. The distribution and chemical nature of mucopolysaccharides in the aforementioned fishes were studied histochemically by employing Periodic Acid Schiff’s in combination with the Alcian Blue (PAS–AB) technique. Columnar epithelial cells lining the mucosa of the stomach including mucosal border were provided with exclusively neutral mucin which was probably involved in the protective functions against acid and enzymes. The different intensities of reaction of Best Carmine (BC) for glycogen in the epithelial lining and gastric glands of the stomach of the aforesaid three fish species under study were discussed. The intense reaction for protein and tryptophan was noticed in the gastric epithelium and gastric glands of M. cavasius probably due to accumulation of zymogen granules in the gastric glands. On the contrary, moderate reaction for protein and tryptophan was associated with the epithelial cells and gastric glands of O. niloticus and G. chapra. The cytoarchitecture and different degrees of localization of mucopolysaccharides, glycogen, protein and tryptophan in the stomach of M. cavasius, O. niloticus and G. chapra were correlated with the functional significance of the region concerned.